An iron-doped nickel hydroxide composite nickel selenide material and its preparation method and application

By using iron-doped nickel hydroxide composite nickel selenide material, the problem of slow kinetics of existing electrocatalysts in alkaline media is solved, and excellent electrolytic performance and good stability under high current density conditions are achieved.

CN115928135BActive Publication Date: 2025-02-18YANAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211454889.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-21
Publication Date
2025-02-18
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

The existing electrocatalysts are slow in kinetics in alkaline media, resulting in slow hydrolysis process, limiting the development of industrial electrolytic cells.

Method used

Iron-doped nickel hydroxide composite nickel selenide material is used to load NiSe nanosheets through a conductive substrate and Fe-doped Ni(OH)2 is grown on its surface to form a composite material with nanosheet morphology.

Benefits of technology

The material exhibits excellent electrolytic properties in alkaline solutions, can operate stably under high current density conditions, meets the needs of industrial electrolytic cells, and remains stable through a 1000-hour durability test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115928135B_ABST
    Figure CN115928135B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrode materials and industrial catalysis technology, and specifically relates to an iron-doped nickel hydroxide composite nickel selenide material and its preparation method and application. The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention comprises a conductive substrate, NiSe nanosheets loaded on the conductive substrate; and Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheets; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal. The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention has the advantages of excellent intrinsic electrocatalytic activity, high electrochemical active area and good stability, and exhibits excellent water electrolysis performance in an alkaline anion exchange membrane water electrolyzer under high current density conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials and industrial catalysis, and specifically relates to an iron-doped nickel hydroxide composite nickel selenide material and a preparation method and application thereof. Background Art

[0002] To solve the global energy crisis and environmental problems caused by the use of fossil fuels, the development of renewable and environmentally friendly energy technologies remains a major challenge facing mankind. Hydrogen energy, as a secondary energy source, has multiple advantages such as diverse sources, zero terminal emissions, and a wide range of uses. Electrochemical water splitting technology uses sustainable clean energy as a power to produce high calorific value hydrogen (H2), providing an effective strategy for converting natural water into chemical fuels. Water splitting involves two half reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. In order to make water electrolysis more energy-efficient, the kinetics of HER or OER can be promoted by reducing the activation energy through electrocatalysts, and can be widely used in industrial production of H2.

[0003] Among various electrocatalysts, platinum has been shown to be the most effective catalyst in acidic media. However, due to the slow kinetics in alkaline media, the dissociation process of water is slow. Therefore, improving the adsorption / dissociation ability of water is the primary task to enhance the kinetics of alkaline HER. Studies have found that transition metal oxides / hydroxides can effectively promote the breaking of H-OH bonds. However, due to their unsatisfactory intrinsic electrocatalytic activity, transition metal oxide / hydroxide electrocatalysts have a slow water dissociation process in alkaline solutions and can only achieve better catalytic HER performance at lower current densities, which largely restricts the development of electrocatalysts for industrial electrolyzers. Summary of the invention

[0004] The purpose of the present invention is to provide an iron-doped nickel hydroxide composite nickel selenide material and a preparation method and application thereof. The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention has the advantages of excellent intrinsic electrocatalytic activity, high electrochemical active area and good stability, and exhibits excellent water electrolysis performance under high current density conditions in alkaline solution.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides an iron-doped nickel hydroxide composite nickel selenide material, comprising a conductive substrate, NiSe nanosheets loaded on the conductive substrate; and Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheets; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal.

[0007] Preferably, in the iron-doped nickel hydroxide composite nickel selenide material, the mass percentage of the Fe element is 0.03-0.05%.

[0008] Preferably, the thickness of the nickel selenide nanosheet is 4 to 4.5 nm; the thickness of the Fe-doped Ni(OH)2 is 3 to 3.5 nm.

[0009] The present invention provides a method for preparing the iron-doped nickel hydroxide composite nickel selenide material described in the above technical solution, comprising the following steps:

[0010] Placing the Ni(OH)2 nanosheet material supported on a conductive substrate in a reducing selenium source aqueous solution to perform a hydrothermal selenization reaction to obtain a NiSe nanosheet material supported on a conductive substrate, wherein the reducing selenium source aqueous solution comprises a selenium source, a reducing agent and water;

[0011] The NiSe nanosheet material supported on the conductive substrate is placed in an electrolyte solution as a working electrode, and Fe-doped Ni(OH)2 is grown on the surface of the NiSe nanosheets of the NiSe nanosheet material supported on the conductive substrate by electrochemical deposition to obtain the iron-doped nickel hydroxide composite nickel selenide material, wherein the electrolyte solution is a mixed aqueous solution of a water-soluble nickel salt and a water-soluble iron salt.

[0012] Preferably, in the electrolyte solution, the molar ratio of the water-soluble nickel salt to the water-soluble iron salt is 7:(0.005-0.02).

[0013] Preferably, the electrochemical deposition adopts a three-electrode system, and during the electrochemical deposition, the potential difference between the working electrode and the reference electrode is -1V.

[0014] Preferably, the electrochemical deposition is constant potential electrochemical deposition; the time of the electrochemical deposition is 300 to 1800 seconds.

[0015] The present invention provides the use of the iron-doped nickel hydroxide composite nickel selenide material described in the above technical scheme or the iron-doped nickel hydroxide composite nickel selenide material prepared by the preparation method described in the above technical scheme as an electrode material in the electrolysis of water to produce hydrogen in an alkaline electrolyte solution, wherein the electrolysis of water to produce hydrogen is carried out in an alkaline electrolyte solution.

[0016] Preferably, the current density of water electrolysis to produce hydrogen in the alkaline electrolyte solution is 100-1000 mA·cm -2 .

[0017] The present invention provides an iron-doped nickel hydroxide composite nickel selenide material, comprising a conductive substrate, NiSe nanosheets loaded on the conductive substrate; and Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheets; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; and the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal. In the iron-doped nickel hydroxide composite nickel selenide material provided by the present invention: on the one hand, Fe is doped into the Ni(OH)2 crystal, which can optimize the electronic structure of the Ni(OH)2 crystal and improve the electrocatalytic intrinsic activity of the iron-doped nickel hydroxide composite nickel selenide material, thereby improving the adsorption / desorption ability of the iron-doped nickel hydroxide composite nickel selenide material for intermediates generated by water electrolysis, including H*, OH*, OOH*, and O*, and promoting HER and OER; on the other hand, the metallic NiSe nanosheets as carriers of Fe-doped Ni(OH)2 can further enhance the conductivity of the iron-doped nickel hydroxide composite nickel selenide material and promote rapid electron transfer; at the same time, NiS Both Ni(OH)2 and Fe-doped Ni(OH)2 are in nanosheet morphology, which is also conducive to the transfer of electrons between NiSe and Ni(OH)2, so that the material provided by the present invention has an ultra-high electron transfer ability; on the other hand, the nanosheet morphology of Fe doped into Ni(OH)2 crystals can expose more water adsorption / dissociation active sites, which is conducive to the generation of a large number of H2 and O2 bubbles for rapid release; fourth, the Fe-doped Ni(OH)2 in the nanosheet morphology on the surface of the iron-doped nickel hydroxide composite nickel selenide material can prevent the leaching of NiSe, so as to improve the stability and durability of the iron-doped nickel hydroxide composite nickel selenide material under high current density in industrial electrolyzers. In summary, the iron-doped nickel hydroxide composite nickel selenide material provided by the present invention has the advantages of excellent intrinsic electrocatalytic activity, high electrochemical active area and good stability, and exhibits excellent electrolytic water hydrogen evolution performance in an alkaline anion exchange membrane water electrolyzer under high current density conditions. The results of the examples show that the iron-doped nickel hydroxide composite nickel selenide material (NiSe / Fe-Ni(OH)2) provided by the present invention can achieve 500 mA·cm2 by constructing an alkaline anion membrane water electrolyzer at only 1.72 V. -2 The current density reaches 1000 mA cm in 1.0 M KOH electrolyte solution. -2 It has a low overpotential (309mV for HER and 315mV for OER), which can meet the needs of large current electrolysis of water; and through a 1000h durability test, its peak current density remains stable without obvious attenuation, showing excellent stability and high conversion efficiency.

[0018] The present invention provides a method for preparing the iron-doped nickel hydroxide composite nickel selenide material described in the above technical solution, comprising the following steps: placing a Ni(OH)2 nanosheet material supported by a conductive substrate in a reducing selenium source aqueous solution, performing a hydrothermal selenization reaction, and obtaining a NiSe nanosheet material supported by a conductive substrate, wherein the reducing selenium source aqueous solution comprises a selenium source, a reducing agent, and water; placing the NiSe nanosheet material supported by the conductive substrate as a working electrode in an electrolyte solution, and growing Fe-doped Ni(OH)2 on the surface of the NiSe nanosheet by electrochemical deposition to obtain the iron-doped nickel hydroxide composite nickel selenide material, wherein the electrolyte solution is a mixed aqueous solution of a water-soluble nickel salt and a water-soluble iron salt. The preparation method provided by the present invention utilizes a hydrothermal reduction reaction and an electrochemical deposition method to obtain a NiSe / Fe-Ni(OH)2 material with high stability, strong gas mass transfer capacity, and excellent electrocatalytic performance, and the preparation method is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XPS graph of the NiSe / Fe-Ni(OH)2 material obtained in Example 1;

[0020] Figure 2 The XRD pattern of the NiSe / Fe-Ni(OH)2 material obtained in Example 1;

[0021] Figure 3 The SEM and TEM images of the NiSe / Fe-Ni(OH)2 material obtained in Example 1;

[0022] Figure 4 The electrochemical hydrogen evolution performance diagram of the NiSe / Fe-Ni(OH)2 material obtained in Example 1 in an alkaline electrolyte solution (1M KOH);

[0023] Figure 5 Impedance diagram of NiSe / Fe-Ni(OH)2 and different electrode materials obtained in Example 1 under negative potential in alkaline electrolyte solution (1M KOH);

[0024] Figure 6 The electrochemical oxygen evolution performance diagram of the NiSe / Fe-Ni(OH)2 electrode obtained in Example 1 in an alkaline electrolyte solution (1M KOH);

[0025] Figure 7 Impedance diagram of NiSe / Fe-Ni(OH)2 and different electrode materials obtained in Example 1 under positive potential in alkaline electrolyte solution (1M KOH);

[0026] Figure 8The electrochemical performance diagram of the NiSe / Fe-Ni(OH)2 material obtained in Example 1 as a bifunctional catalytic electrode for electrolyzing water in an alkaline electrolytic cell;

[0027] Fig. 9 This is the electrochemical performance diagram of the NiSe / Fe-Ni(OH)2 material obtained in Example 1 as a bifunctional catalytic electrode in an alkaline AEM electrolyzer for electrolysis of water at 85°C. DETAILED DESCRIPTION

[0028] The present invention provides an iron-doped nickel hydroxide composite nickel selenide material, comprising a conductive substrate, NiSe nanosheets loaded on the conductive substrate; and Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheets; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal.

[0029] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0030] The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention comprises a conductive substrate. In the present invention, the conductive substrate is preferably foamed nickel.

[0031] The iron-doped nickel hydroxide composite nickel selenide material provided by the invention comprises NiSe nanosheets loaded on the conductive substrate.

[0032] In the present invention, the NiSe nanosheets are grown on the conductive substrate.

[0033] In the present invention, in the iron-doped nickel hydroxide composite nickel selenide material (including the conductive substrate), the mass percentage of the nickel selenide nanosheets calculated based on the Se content is preferably 9.44wt%.

[0034] In the present invention, the thickness of the nickel selenide nanosheet is 4 to 4.5 nm.

[0035] The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention comprises Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheet; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal.

[0036] In the present invention, the Fe-doped Ni(OH)2 grows on the surface of the NiSe nanosheets.

[0037] In the present invention, in the iron-doped nickel hydroxide composite nickel selenide material (including the conductive substrate), the mass percentage of the Fe element is preferably 0.03-0.05%, and more preferably 0.035-0.045%.

[0038] In the present invention, the thickness of the Fe-doped Ni(OH)2 is 3 to 3.5 nm.

[0039] The iron-doped nickel hydroxide composite nickel selenide material provided by the present invention loads Fe-doped Ni(OH)2 (labeled as NiSe / Fe-Ni(OH)2) on the surface of NiSe nanosheets, which has abundant active sites and ultra-high electron transfer ability. Fe doping improves the electrocatalytic intrinsic activity of NiSe / Fe-Ni(OH)2, which can meet the requirements of industrial high current density electrochemical decomposition of water to produce hydrogen.

[0040] The present invention provides a method for preparing the iron-doped nickel hydroxide composite nickel selenide material described in the above technical solution, comprising the following steps:

[0041] Placing the Ni(OH)2 nanosheet material supported on a conductive substrate in a reducing selenium source aqueous solution to perform a hydrothermal selenization reaction to obtain a NiSe nanosheet material supported on a conductive substrate, wherein the reducing selenium source aqueous solution comprises a selenium source, a reducing agent and water;

[0042] The NiSe nanosheet material loaded on the conductive substrate is placed in an electrolyte solution as a working electrode, and Fe-doped Ni(OH)2 is grown on the surface of the NiSe nanosheet by electrochemical deposition to obtain the iron-doped nickel hydroxide composite nickel selenide material. The electrolyte solution is a mixed aqueous solution of a water-soluble nickel salt (hereinafter referred to as the first water-soluble nickel salt) and a water-soluble iron salt.

[0043] The present invention places a Ni(OH)2 nanosheet material supported on a conductive substrate in a reducing selenium source aqueous solution to perform a hydrothermal selenization reaction to obtain a NiSe nanosheet material supported on a conductive substrate. The reducing selenium source aqueous solution comprises a selenium source, a reducing agent and water.

[0044] In the present invention, the method for preparing the conductive substrate-supported Ni(OH)2 nanosheet material preferably comprises the following steps:

[0045] The conductive substrate is placed in a nickel source solution for hydrothermal reaction to obtain a Ni(OH)2 nanosheet material supported by the conductive substrate. The nickel source solution includes a second water-soluble nickel salt, a plasticizer and water.

[0046] In the present invention, the conductive substrate is preferably nickel foam (NF), and the dimensions of width×length of the nickel foam (NF) are 3 cm×4 cm.

[0047] In the present invention, before carrying out the hydrothermal reaction, the present invention preferably pre-treats the conductive substrate. In the present invention, the pre-treatment preferably comprises the following steps: washing the conductive substrate with hydrochloric acid solution, water washing and ethanol washing in sequence. In the present invention, the molar concentration of the hydrochloric acid solution used in the hydrochloric acid solution washing is preferably 3 mol / L; the hydrochloric acid solution washing is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 15 min. The present invention preferably removes the oxide layer on the surface of the conductive substrate by washing with the hydrochloric acid solution. In the present invention, the water washing is preferably deionized water washing; the specific implementation of the water washing is preferably rinsing. The specific implementation of the ethanol washing is preferably rinsing.

[0048] In the present invention, in the nickel source solution, the second water-soluble nickel salt is preferably NiCl2·6H2O.

[0049] In the present invention, in the nickel source solution, the plasticizer is preferably NH4F and CO(NH2)2. The molar ratio of NH4F to CO(NH2)2 is preferably 1:2.

[0050] In the present invention, in the nickel source solution, the water is preferably deionized water.

[0051] In the present invention, in the nickel source solution, the ratio of the amount of the second water-soluble nickel salt to the volume of the water is preferably 3 mmol:35 mL.

[0052] In the present invention, in the nickel source solution, the molar ratio of the second water-soluble nickel salt to the plasticizer is preferably 1:5.

[0053] In the present invention, in the nickel source solution, the ratio of the amount of the plasticizer to the volume of the water is preferably 15 mmol:35 mL.

[0054] In the present invention, the method for preparing the nickel source solution preferably comprises: dissolving the second water-soluble nickel salt and the plasticizer in water, and stirring for 30 minutes to obtain the nickel source solution.

[0055] In the present invention, the hydrothermal reaction is preferably carried out in a reactor with a PTFE liner. The volume of the reactor with a PTFE liner is preferably 100 mL.

[0056] In the present invention, the conductive substrate is preferably placed in a nickel source solution at an angle to perform a hydrothermal reaction. In the present invention, when the conductive substrate is placed in the nickel source solution, the angle between the conductive substrate and the horizontal plane is not 90°.

[0057] In the present invention, the hydrothermal reaction is preferably carried out in a closed environment. The temperature of the hydrothermal reaction is preferably 180° C.; and the holding time of the hydrothermal reaction is preferably 6 hours.

[0058] In the present invention, after the hydrothermal reaction is completed, the present invention preferably removes the obtained Ni(OH)2 nanosheet material supported on the conductive substrate from the hydrothermal reaction solution cooled to room temperature. The present invention preferably sequentially washes the obtained Ni(OH)2 nanosheet material supported on the conductive substrate with water and ethanol. In the present invention, the water washing is preferably deionized water washing.

[0059] In the present invention, the reduced selenium source aqueous solution comprises a selenium source, a reducing agent and water. The selenium source is preferably selenium powder. The reducing agent is preferably NaBH. The mass ratio of the selenium source to the reducing agent is preferably 0.1:0.096. In the present invention, in the reduced selenium source aqueous solution, the water is preferably deionized water; the mass ratio of the selenium source to the volume of the water is preferably 0.1g:35mL.

[0060] In the present invention, the method for preparing the reducing selenium source aqueous solution preferably comprises the following steps: dissolving the selenium source and the reducing agent in water and stirring and mixing for 2 hours. In the present invention, the selenium source and the reducing agent are preferably dissolved in water and stirred and mixed for 2 hours until the solution color is red-black, and the selenium powder is completely reduced.

[0061] In the present invention, the hydrothermal selenization reaction is preferably carried out in a reactor with a PTFE lining. The volume of the reactor with a PTFE lining is preferably 100 mL.

[0062] In the present invention, the temperature of the hydrothermal selenization reaction is preferably 180° C.; the insulation time of the hydrothermal selenization reaction is preferably 4 hours.

[0063] In the present invention, after the hydrothermal selenization reaction is completed, the present invention preferably takes out the obtained NiSe nanosheet material supported by the conductive substrate from the hydrothermal selenization reaction solution cooled to room temperature. The present invention preferably sequentially washes the obtained NiSe nanosheet material supported by the conductive substrate with water, ethanol and dries. In the present invention, the water washing is preferably deionized water washing. The drying is preferably vacuum drying.

[0064] In the present invention, the NiSe nanosheet array is distributed on the conductive substrate.

[0065] After obtaining the NiSe nanosheet material supported on a conductive substrate, the present invention places the NiSe nanosheet material supported on a conductive substrate as a working electrode in an electrolyte solution, and uses electrochemical deposition to grow Fe-doped Ni(OH)2 on the surface of the NiSe nanosheets of the NiSe nanosheet material supported on the conductive substrate to obtain the iron-doped nickel hydroxide composite nickel selenide material, wherein the electrolyte solution is a mixed aqueous solution of a water-soluble nickel salt (hereinafter referred to as the first water-soluble nickel salt) and a water-soluble iron salt.

[0066] In the present invention, the electrochemical deposition is preferably constant potential electrochemical deposition.

[0067] In the present invention, the first water-soluble nickel salt is preferably NiCl2·6H2O.

[0068] In the present invention, the water-soluble iron salt is preferably FeCl3.

[0069] In the present invention, in the electrolyte solution, the molar ratio of the water-soluble nickel salt to the water-soluble iron salt is 7:(0.005-0.02), preferably 7:0.01.

[0070] In the present invention, the electrolyte solution is preferably composed of 50 mL of a 0.7 mol / L NiCl2·6H2O aqueous solution and 50 μL of a 1.0 mol / L FeCl3 aqueous solution.

[0071] In the present invention, the electrochemical deposition adopts an electrode system, and during the electrochemical deposition, the potential difference of the working electrode relative to the reference electrode is preferably -1 V. In the present invention, the reference electrode is preferably Ag / AgCl; the counter electrode in the three-electrode system is preferably a platinum sheet.

[0072] In the present invention, the electrochemical deposition time is preferably 300 to 1800 seconds.

[0073] The present invention provides the use of the iron-doped nickel hydroxide composite nickel selenide material described in the above technical scheme or the iron-doped nickel hydroxide composite nickel selenide material prepared by the preparation method described in the above technical scheme as an electrode material in electrolyzing water to produce hydrogen in an alkaline electrolyte solution.

[0074] In the present invention, the current density of the alkaline electrolyte solution during water electrolysis to produce hydrogen is 100 to 1000 mA cm -2 .

[0075] In the present invention, the alkaline electrolyte solution is preferably a 1 mol / L KOH solution.

[0076] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0077] Example 1

[0078] The nickel foam (3cm×4cm) was washed with 3M HCl solution by ultrasonic treatment for 15min, and then rinsed with deionized water and ethanol to obtain the pretreated NF. 3mmol NiCl2·6H2O, 5mmol NH4F and 10mmol CO(NH2)2 were dissolved in 35mL deionized water and placed in 100mL PTFE liner. After stirring for 30 minutes, the pretreated NF was placed in the PTFE liner at a certain angle and then placed in an autoclave. It was sealed and kept at 180℃ for 6h. After the autoclave was cooled to room temperature, the obtained NF-loaded Ni(OH)2 nanosheet material was washed several times with deionized water and ethanol.

[0079] In a PTFE-lined stainless steel autoclave (100 mL), 0.1 g of selenium powder and 0.096 g of NaBH were dissolved in 35 mL of deionized water and stirred for 2 h to ensure that the selenium powder was completely reduced to obtain a reducing selenium source aqueous solution. The NF-loaded Ni(OH)2 nanosheet material was transferred to a PTFE-lined stainless steel autoclave for hydrothermal selenization. The hydrothermal selenization reaction was carried out at 180 ° C for 4 h. After naturally cooling to room temperature, the obtained NF-loaded NiSe nanosheet array was repeatedly washed with water and ethanol, and then dried in a vacuum.

[0080] At room temperature, an electrolyte solution is obtained by mixing 50 mL of a 0.7 mol / L NiCl2·6H2O aqueous solution and 50 μL of a 1.0 mol / L FeCl3 aqueous solution. A three-electrode system is used for constant potential electrochemical deposition, wherein the working electrode is a NiSe nanosheet loaded with NF, the reference electrode is Ag / AgCl, and the counter electrode is preferably a platinum sheet. Electrochemical deposition is performed at a potential difference of -1.0 V relative to Ag / AgCl for 1200 s to prepare a NiSe / Fe-Ni(OH)2 material.

[0081] Example 2

[0082] The nickel foam (3cm×4cm) was washed with 3M HCl solution by ultrasonic treatment for 15min, and then rinsed with deionized water and ethanol to obtain the pretreated NF. 3mmol NiCl2·6H2O, 5mmol NH4F and 10mmol CO(NH2)2 were dissolved in 35mL deionized water and placed in 100mL PTFE liner. After stirring for 30 minutes, the pretreated NF was placed in the PTFE liner at a certain angle and then placed in an autoclave. It was sealed and kept at 180℃ for 6h. After the autoclave was cooled to room temperature, the obtained NF-loaded Ni(OH)2 nanosheet material was washed several times with deionized water and ethanol.

[0083] In a PTFE-lined stainless steel autoclave (100 mL), 0.1 g of selenium powder and 0.096 g of NaBH were dissolved in 35 mL of deionized water and stirred for 2 h to ensure that the selenium powder was completely reduced to obtain a reducing selenium source aqueous solution. The NF-loaded Ni(OH)2 nanosheet material was transferred to a PTFE-lined stainless steel autoclave for hydrothermal selenization. The hydrothermal selenization reaction was carried out at 180 ° C for 4 h. After naturally cooling to room temperature, the obtained NF-loaded NiSe nanosheet array was repeatedly washed with water and ethanol, and then dried in a vacuum.

[0084] At room temperature, an electrolyte solution is obtained by mixing 50 mL of a 0.7 mol / L NiCl2·6H2O aqueous solution and 50 μL of a 1.0 mol / L FeCl3 aqueous solution. A three-electrode system is used for constant potential electrochemical deposition, wherein the working electrode is a NiSe nanosheet loaded with NF, the reference electrode is Ag / AgCl, and the counter electrode is preferably a platinum sheet. Electrochemical deposition is performed at a potential difference of -1.0 V between the working electrode and Ag / AgCl, and the deposition time is 800 s to prepare a NiSe / Fe-Ni(OH)2 material.

[0085] Example 3

[0086] The nickel foam (3cm×4cm) was washed with 3M HCl solution by ultrasonic treatment for 15min, and then rinsed with deionized water and ethanol to obtain the pretreated NF. 3mmol NiCl2·6H2O, 5mmol NH4F and 10mmol CO(NH2)2 were dissolved in 35mL deionized water and placed in 100mL PTFE liner. After stirring for 30 minutes, the pretreated NF was placed in the PTFE liner at a certain angle and then placed in an autoclave. It was sealed and kept at 180℃ for 6h. After the autoclave was cooled to room temperature, the obtained NF-loaded Ni(OH)2 nanosheet material was washed several times with deionized water and ethanol.

[0087] In a PTFE-lined stainless steel autoclave (100 mL), 0.1 g of selenium powder and 0.096 g of NaBH were dissolved in 35 mL of deionized water and stirred for 2 h to ensure that the selenium powder was completely reduced to obtain a reducing selenium source aqueous solution. The NF-loaded Ni(OH)2 nanosheet material was transferred to a PTFE-lined stainless steel autoclave for hydrothermal selenization. The hydrothermal selenization reaction was carried out at 180 ° C for 4 h. After naturally cooling to room temperature, the obtained NF-loaded NiSe nanosheet array was repeatedly washed with water and ethanol, and then dried in a vacuum.

[0088] At room temperature, an electrolyte solution is obtained by mixing 50 mL of a 0.7 mol / L NiCl2·6H2O aqueous solution and 50 μL of a 1.0 mol / LFeCl3 aqueous solution. A three-electrode system is used for constant potential electrochemical deposition, wherein the working electrode is a NiSe nanosheet loaded with NF, the reference electrode is Ag / AgCl, and the counter electrode is preferably a platinum sheet. Electrochemical deposition is performed at a potential difference of -1.0 V relative to Ag / AgCl for 1500 s to prepare a NiSe / Fe-Ni(OH)2 material.

[0089] Comparative Example 1

[0090] The nickel foam (3cm×4cm) was washed with 3M HCl solution by ultrasonic treatment for 15min, and then rinsed with deionized water and ethanol to obtain the pretreated NF. 3mmol NiCl2·6H2O, 5mmol NH4F and 10mmol CO(NH2)2 were dissolved in 35mL deionized water and placed in 100mL PTFE liner. After stirring for 30 minutes, the pretreated NF was placed in the PTFE liner at a certain angle and then placed in an autoclave. It was sealed and kept at 180℃ for 6h. After the autoclave was cooled to room temperature, the obtained NF-loaded Ni(OH)2 nanosheet material was washed several times with deionized water and ethanol.

[0091] In a PTFE-lined stainless steel autoclave (100 mL), 0.1 g of selenium powder and 0.096 g of NaBH were dissolved in 35 mL of deionized water and stirred for 2 h to ensure that the selenium powder was completely reduced to obtain a reducing selenium source aqueous solution. The NF-loaded Ni(OH)2 nanosheet material was transferred to a PTFE-lined stainless steel autoclave for hydrothermal selenization. The hydrothermal selenization reaction was carried out at 180 ° C for 4 h. After naturally cooling to room temperature, the obtained NF-loaded NiSe nanosheet array was repeatedly washed with water and ethanol, and then dried in a vacuum.

[0092] At room temperature, 50 mL of 0.7 mol / L NiCl2·6H2O aqueous solution was used as the electrolyte solution; a three-electrode system was used for constant potential electrochemical deposition, the working electrode was NiSe nanosheets loaded on NF, the reference electrode was Ag / AgCl, and the counter electrode was preferably a platinum sheet; electrochemical deposition was carried out at a potential difference of -1.0 V relative to Ag / AgCl for 1200 s to prepare NiSe / Ni(OH)2 material.

[0093] Application Examples

[0094] Electrode materials prepared in Example 1 and Comparative Example 1 were used to carry out water electrolysis and hydrogen evolution experiments in an alkaline anion exchange membrane water electrolyzer; the electrolyte was 1M KOH.

[0095] The experimental conditions are as follows: a typical three-electrode system is used, and NiSe / Fe-Ni(OH)2 prepared in Example 1 and NiSe / Ni(OH)2 prepared in Comparative Example 1 are used as working electrodes, a graphite rod electrode is used as a counter electrode, and a mercury / mercury oxide electrode (KOH and natural seawater) and a saturated calomel electrode (H2SO4 and PBS) are used as reference electrodes; all voltages relative to RHE are converted using the formula shown in Formula 1 or Formula 2:

[0096] E RHE =E Hg / HgO +0.059pH+0.098V (KOH and natural seawater) Formula 1;

[0097] E RHE =E SCE +0.059pH+0.242V(H2SO4 and PBS) Formula 2.

[0098] During the test, the linear voltammetric scanning test scanning speed is 2mV / s.

[0099] Figure 1 XPS graphs of NiSe loaded on NF prepared in Example 1, NiSe / Ni(OH)2 prepared in Comparative Example 1, and NiSe / Fe-Ni(OH)2 prepared in Example 1, which can analyze the surface composition and chemical valence state of NiSe / Fe-Ni(OH)2; Figure 1 (a) in the figure clearly shows the Ni 2p high-resolution spectra corresponding to NiSe, NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2. In NiSe, the Ni 2p peaks at 855.2eV and 872.8eV correspond to the characteristic peaks of Ni 2p3 / 2 and Ni 2p1 / 2, respectively, which are attributed to Ni 2+After the electrodeposition of NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2, Ni 2p shifted slightly by 0.36 eV, which may be caused by the appearance of Ni(OH)2. Figure 1 As shown in (b), two pairs of strong characteristic peaks are observed in NiSe at 58.3eV and 59.4eV, corresponding to Se 2- 3d5 / 2 and Se 2- 3d3 / 2. For NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2 electrodes, the Se 3d spectrum has almost no peak, which may be caused by the Ni(OH)2 covering the upper layer. Figure 1 In (c), the two peaks at 713.1eV and 725.2eV are attributed to Fe 3+ 2p3 / 2 and Fe 3+ 2p1 / 2, the satellite peak is attributed to 716.5eV (denoted as Sat.). The peak at 706.9 is attributed to Fe 2+ , showing different valence states of Fe 2+ and Fe 3+ The presence of the coexisting NiSe / Fe-Ni(OH)2 catalysts indicates that the Fe element is doped into the Ni(OH)2 lattice.

[0100] Figure 2 XRD patterns of NiSe loaded on NF prepared in Example 1, NiSe / Ni(OH)2 prepared in Comparative Example 1, and NiSe / Fe-Ni(OH)2 prepared in Example 1; Figure 2 The characteristic diffraction peak of NiSe can be seen in the electrodeposition of Ni(OH)2. After adding a trace amount of Fe to Ni(OH)2, the diffraction peak of Ni(OH)2 was found, but no diffraction peak about Fe was found. After adding a trace amount of Fe to the electrodeposition solution, the crystallization peak did not change significantly, indicating that no new substances were produced during the deposition process. It is proved that Example 1 successfully doped Fe into Ni(OH)2 and successfully synthesized NiSe / Fe-Ni(OH)2 electrode material.

[0101] Figure 3 Figure (a) is the SEM image of NF-loaded NiSe. Figure 3 (b) is the SEM image of NiSe / Ni(OH)2; Figure 3 (c) in the figure is the SEM image of NiSe / Fe-Ni(OH)2. Figure 3 In (a)-(c), obvious nanosheets can be seen. Figure 3 (d)-(f) are TEM images of NiSe, NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2 respectively. Figure 3 (c) and Figure 3 As can be seen in (f), the Fe-doped Ni(OH)2 nanosheets become thinner compared to NiSe / Ni(OH)2. Figure 3 (g)-(i) are HRTEM images of NF-loaded NiSe, NiSe / Ni(OH)2, and NiSe / Fe-Ni(OH)2, respectively. From the high-resolution HRTEM image, the lattice fringe spacing of 0.289nm belongs to the NiSe(300) crystal plane. The HRTEM image of NiSe / Ni(OH)2 shows two different lattice fringes of 0.20 and 0.15nm, which match well with the (131) plane of NiSe and the (110) plane of Ni(OH)2, respectively. After trace Fe doping, it can be seen that the lattice spacing of NiSe does not change, while the lattice fringes of Ni(OH)2 become 0.15nm and 0.24nm, corresponding to the (110) and (011) lattice planes, respectively. This result further confirms that trace Fe is effectively doped into Ni(OH)2 to form NiSe / Fe-Ni(OH)2. From Figure 3 (j) The energy dispersive X-ray spectroscopy element mapping also confirms that Ni, Se, O and Fe elements are uniformly dispersed in NiSe / Fe-Ni(OH)2, indicating that Fe is successfully doped.

[0102] Figure 4 This is a comparison chart of the electrochemical hydrogen evolution performance of NiSe / Fe-Ni(OH)2 electrode materials; Figure 4 In (a) and (b), NF represents nickel foam, Ni(OH)2 is the NF-loaded Ni(OH)2 nanosheet material prepared in Example 1, NiSe is the NF-loaded NiSe nanosheet prepared in Example 1; NiSe / Ni(OH)2 is the electrode material prepared in Comparative Example 1, NiSe / Fe-Ni(OH)2 is the electrode material prepared in Example; Pt / C is a commercial catalyst (Pt / C catalyst is dripped onto nickel foam for testing), Figure 4 (c) and (d) are the properties of the NiSe / Fe-Ni(OH)2 electrode materials prepared in the examples; Figure 4 It can be seen that the NiSe / Fe-Ni(OH)2 electrode exhibits better hydrogen evolution performance in 1M KOH than NF-loaded NiSe and NiSe / Ni(OH)2, and can reach 10 mA cm at overpotentials of 76 mV and 309 mV, respectively. -2 and 500mA·cm -2 The NiSe / Fe-Ni(OH)2 electrode also exhibited the lowest Tafel slope and had the fastest reaction kinetics. In addition, long-term cyclic voltammetry and it tests revealed that the NiSe / Fe-Ni(OH)2 electrode had excellent stability.

[0103] Figure 5 The impedance tests of NF, NF-loaded NiSe, NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2 under hydrogen evolution potential in 1M KOH were performed; Figure 5 It can be seen that the arc radius of NiSe / Fe-Ni(OH)2 in 1M KOH is the smallest, indicating that NiSe / Fe-Ni(OH)2 has the smallest electrochemical impedance and the strongest electron transfer ability.

[0104] Figure 6 The comparison chart of electrochemical oxygen evolution performance of NiSe / Fe-Ni(OH)2 electrode materials; Figure 6 It can be seen that the NiSe / Fe-Ni(OH)2 electrode exhibits better oxygen evolution performance in 1M KOH than NF-loaded NiSe and NiSe / Ni(OH)2, and can reach 10 mA cm at overpotentials of 196 mV and 325 mV, respectively. -2 and 500mA·cm -2 The NiSe / Fe-Ni(OH)2 electrode also exhibited the lowest Tafel slope and had the fastest reaction kinetics. In addition, long-term cyclic voltammetry and it tests revealed that the NiSe / Fe-Ni(OH)2 electrode had excellent stability.

[0105] Figure 7 The impedance tests of NF, NF-loaded NiSe, NiSe / Ni(OH)2 and NiSe / Fe-Ni(OH)2 under oxygen evolution potential in 1M KOH were performed; Figure 7 It can be seen that the arc radius of NiSe / Fe-Ni(OH)2 in 1M KOH is the smallest, indicating that the electrochemical impedance of NiSe / Fe-Ni(OH)2 is the smallest and exhibits the best electron transfer ability.

[0106] Figure 8 NF in the above represents nickel foam, Ni(OH)2 is the NF-loaded Ni(OH)2 nanosheet material prepared in Example 1, and NiSe is the NF-loaded NiSe nanosheet prepared in Example 1; NiSe / Ni(OH)2 is the electrode material prepared in Comparative Example 1, and NiSe / Fe-Ni(OH)2 is the electrode material prepared in Example; Figure 8 This is the electrochemical performance diagram of the two-electrode system for water electrolysis based on NiSe / Fe-Ni(OH)2. Figure 8 The upper left figure in the figure is the LSV polarization curve of NiSe||NiSe, NiSe / Ni(OH)2||NiSe / Ni(OH)2, NiSe / Fe-Ni(OH)2||NiSe / Fe-Ni(OH)2 and Pt / C||IrO2. Figure 8 In the upper left figure, we can see that the NiSe / Fe-Ni(OH)2 electrode reaches 100 and 500 mA cm -2 When the power is off, only the smaller voltages of 1.69V and 1.83V need to be provided. Figure 8 The upper right part of the figure shows the hydrogen and oxygen production at different current densities. Figure 8 It can be seen from the upper right figure in the figure that the volume of H2 is always twice that of O2, which is very close to the theoretical value, showing a Faraday efficiency close to 100%. Figure 8 The lower part of the figure shows the NiSe / Fe-Ni(OH)2 two-electrode system at 500 / 600 mA·cm -2 The 1000-hour stability test under stable conditions also showed excellent electrochemical water splitting performance.

[0107] Fig. 9 The electrochemical performance diagram of NiSe / Fe-Ni(OH)2 in an alkaline anion exchange membrane electrolyzer at 85℃. Fig. 9 It can be seen that NiSe / Fe-Ni(OH)2 exhibits the best water electrolysis performance; at 500mA·cm -2 When the voltage is only 1.72V, it shows the best electrochemical water splitting performance compared with NF (2.57V), NiSe (2.16V), NiSe / Ni(OH)2 (1.88V) and IrO2 (2.01V). Under different constant current densities, the electrolytic cell potential using NiSe / Fe-Ni(OH)2 electrodes is always lower than the electrolytic cell potential using other electrocatalysts. After 100 hours of stability testing, there is no obvious attenuation trend, showing good potential for industrial application.

[0108] In summary, the NiSe / Fe-Ni(OH)2 bifunctional electrode material prepared by the present invention can achieve efficient water electrolysis in alkaline electrolytes and can meet the requirements of industrial large current water electrolysis and hydrogen production under alkaline conditions. The electrode material has excellent intrinsic activity. The electronic structure of Ni(OH)2 is adjusted by trace Fe doping, the adsorption and desorption of intermediates are optimized, and it is compounded with metallic NiSe to promote electron transfer between NiSe and Ni(OH)2. We first synthesized the NiSe precursor, and then obtained the NiSe / Fe-Ni(OH)2 nanosheet composite material by electrochemical deposition. When we applied the composite material to the electrode material of industrial alkaline water electrolysis, it showed the advantages of excellent intrinsic activity, high electrochemical active area and good stability. Since NiSe / Fe-Ni(OH)2 has the ability to withstand large currents, it also shows excellent water electrolysis and hydrogen evolution performance in alkaline anion exchange membrane water electrolyzers, which is conducive to direct coupling with unstable output power such as solar energy, wind energy, and tidal energy for water electrolysis. This work not only demonstrates an efficient and industrially viable strategy for ultra-low voltage water electrolysis at high current density, but also provides ideas for the development of advanced composite electrode materials based on non-precious transition metals.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an iron-doped nickel hydroxide composite nickel selenide material, characterized in that: The iron-doped nickel hydroxide composite nickel selenide material comprises a conductive substrate, a NiSe nanosheet loaded on the conductive substrate; and Fe-doped Ni(OH)2 loaded on the surface of the NiSe nanosheet; the morphology of the Fe-doped Ni(OH)2 is a nanosheet; the Fe element in the Fe-doped Ni(OH)2 is doped into the Ni(OH)2 crystal; the preparation method of the iron-doped nickel hydroxide composite nickel selenide material comprises the following steps: The Ni(OH)2 nanosheet material supported on the conductive substrate is placed in a reducing selenium source aqueous solution to perform a hydrothermal selenization reaction to obtain a NiSe nanosheet material supported on the conductive substrate, wherein the reducing selenium source aqueous solution comprises a selenium source, a reducing agent and water; the selenium source is selenium powder; and the reducing agent is NaBH4; The NiSe nanosheet material loaded on the conductive substrate is placed in an electrolyte solution as a working electrode, and Fe-doped Ni(OH)2 is grown on the surface of the NiSe nanosheet by electrochemical deposition to obtain the iron-doped nickel hydroxide composite nickel selenide material. The electrolyte solution is a mixed aqueous solution of a water-soluble nickel salt and a water-soluble iron salt.

2. The method for preparing the iron-doped nickel hydroxide composite nickel selenide material according to claim 1, characterized in that: In the iron-doped nickel hydroxide composite nickel selenide material, the mass percentage content of the Fe element is 0.03-0.05%.

3. The method for preparing the iron-doped nickel hydroxide composite nickel selenide material according to claim 1, characterized in that: The thickness of the nickel selenide nanosheet is 4 to 4.5 nm; the thickness of the Fe-doped Ni(OH)2 is 3 to 3.5 nm.

4. The preparation method according to claim 1, characterized in that: In the electrolyte solution, the molar ratio of the water-soluble nickel salt to the water-soluble iron salt is 7:(0.005-0.02).

5. The preparation method according to claim 1, characterized in that: The electrochemical deposition adopts a three-electrode system. During the electrochemical deposition, the potential difference between the working electrode and the reference electrode is -1V.

6. The preparation method according to claim 1 or 5, characterized in that: The electrochemical deposition is constant potential electrochemical deposition; the time of the electrochemical deposition is 300 to 1800 seconds.

7. Use of the iron-doped nickel hydroxide composite nickel selenide material prepared by the preparation method according to any one of claims 1 to 6 as an electrode material in the electrolysis of water to produce hydrogen in an alkaline electrolyte solution, wherein the electrolysis of water to produce hydrogen is carried out in an alkaline electrolyte solution.

8. The use according to claim 7, characterized in that: The current density during the electrolysis of water to produce hydrogen is 100-1000 mA·cm -2 .